Parthenolide Induces Reactive Oxygen Species-Mediated Autophagic Cell Death in Human Osteosarcoma Cells - Chen Yang (Cellular Physiology and Biochemistry, 2016)
Background and Aim: Osteosarcoma is a devastating tumor of bone, primarily affecting adolescents. Parthenolide, a naturally occurring small molecule that interferes with NF-κB signaling, has recently attracted considerable attention because of its pharmacological action involving anti-cancer effects. However, the mechanism of the cytotoxic effect exerted by parthenolide on tumor cells is not clearly defined today. Methods: In this study, the effects of parthenolide were evaluated and characterized in human osteosarcoma cancer cell. Cell viability was assessed by CCK-8. Apoptosis was assessed by Annexin V-FITC/PI Flow cytometry assay. Relative quantitative real-time PCR and western blot were used to determine the expressions of genes and proteins. Results: Our results suggest that parthenolide did not cause caspase-dependent cell death in osteosarcoma cancer cells, as indicated by the absence of significant early apoptosis as well as caspase-3 cleavage. Instead, parthenolide increased the autophagy and mitophagy, as characterized by increased PINK1 and Parkin translocation to mitochondria and enhanced autophagy proteins. The induction of autophagy by parthenolide was associated with the increase of reactive oxygen species (ROS). ROS antioxidants N-acetylcysteine (NAC) attenuated parthenolide-induced autophagy activity. Conclusions: Our findings unveil a novel mechanism of drug action by parthenolide in osteosarcoma cancer cells and suggest a potential value of treating osteosarcoma cancer through a caspase-independent autophagic cell death by ROS activation.